2019
DOI: 10.1097/bsd.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Clinically Important Difference and Substantial Clinical Benefit Using PROMIS CAT in Cervical Spine Surgery

Abstract: Study Design: This was a prospective cohort study. Objective: The objective of this study was to establish minimal clinically important difference (MCID) and substantial clinical benefit (SCB) thresholds for Patient-Reported Outcomes Measurement Information System (PROMIS) in cervical spine pathology. Summary of Background Data: PROMIS enables improved psychometric properties with reduced questionnaire burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 33 publications
1
77
0
Order By: Relevance
“…In particular, many of the early investigations centered on the MCID of the PROMIS Physical Function questionnaire for spine, foot and ankle, and hand surgery. 5,16,32,34 In a psychometric comparison of the PROMIS Physical Function with the ASES score in patients undergoing shoulder arthroplasty, Fu et al 10 found that the PROMIS Physical Function was psychometrically inferior to the ASES and that the PROMIS UE may be a more appropriate PROMIS instrument in patients with shoulder disability. To our knowledge, this is the first study to evaluate clinically significant outcome measures of the PROMIS UE.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many of the early investigations centered on the MCID of the PROMIS Physical Function questionnaire for spine, foot and ankle, and hand surgery. 5,16,32,34 In a psychometric comparison of the PROMIS Physical Function with the ASES score in patients undergoing shoulder arthroplasty, Fu et al 10 found that the PROMIS Physical Function was psychometrically inferior to the ASES and that the PROMIS UE may be a more appropriate PROMIS instrument in patients with shoulder disability. To our knowledge, this is the first study to evaluate clinically significant outcome measures of the PROMIS UE.…”
Section: Discussionmentioning
confidence: 99%
“…All PROMs were collected preoperatively and at 6 weeks, 12 weeks, 6 months, and 1 year postoperatively. Assessment of significant improvements as perceived by the patient was collected through MCID achievement by comparing the improvement from preoperative to postoperative scores (Delta) with established thresholds from the literature: 2.6 (VAS neck); 20 4.1 (VAS arm); 20 17.3 (NDI); 20 8.1 (SF-12 PCS); 20 4.7 www.e-neurospine.org 379 (SF-12 MCS); 20 4.5 (PROMIS PF); 21 3.0 (PHQ-9). 22…”
Section: Data Collectionmentioning
confidence: 99%
“…MCID achievement was determined through comparison of the difference in preoperative and postoperative PROM scores to a pre-established value. MCID values from Parker et al 14 were used for VAS neck (2.6), VAS arm (4.1), NDI (17.3% or 8.5), and SF-12 PCS (8.1); whereas Steinhaus et al 15 established a PROMIS PF MCID of 4.5.…”
Section: Minimum Clinically Important Differencementioning
confidence: 99%